Development of Cutaneous Leishmaniasis after Leishmania Skin Test - Paulo R. Machado; Augusto M. Carvalho; Gustavo U. Machado; Marina L. Dantas; Sérgio Arruda (Case Reports in Medicine)
Thirty-year-old female with a previous history of a cutaneous ulcer suspicious of leishmaniasis 20 years ago presented with a new complaint of a depressed papular lesion 8×7 mm in the right lower extremity. The lesion was of 10-day duration. Because early cutaneous leishmaniasis (CL) lesions may have a non-ulcerated appearance, a Leishmania skin test (LST) was performed on the forearm with a strong positive result (38×32 mm). After 8 days, the lesion in the leg, which was diagnosed as folliculitis, completely healed. However, a typical CL ulcer (26×24 mm) developed at the LST site. Histopathology of the new lesion did not identifiy parasites, but the findings were consistent with a diagnosis of CL. Further analysis identified amastigotes by immunohistochemical stain. Mononuclear cells harvested from the patient were stimulated with Leishmania antigen and showed high levels of production of both tumor necrosis factor-alpha (TNF-α) and interferon-gamma (IFN-γ): 2,943 pg/mL and 2,313 pg/mL, respectively. After 40 days of treatment with antimony and pentoxifylline, the ulcer resolved. The development of CL at the LST site suggests a strong Th1 immune response, and it is an in vivo documentation of the role of the host immune response in the pathology of CL. It teaches us that LST should be cautiously, if at all, used in patients with self-healing CL ulcers.